Penyuluhan Fisioterapi tentang Deteksi Dini dan Pencegahan Skoliosis pada Siswa di SDN Polowijen 1 Kota Malang - Warsito Eko Prasetyo; Rakhmad Rosadi; Ika Arma Rani (Universitas 45 Surabaya, 2024)
Child development is currently experiencing significant progress. However, children often experience posture problems such as scoliosis, lordosis, kyphosis, and shoulder asymmetry. If not treated immediately, this problem can continue into adulthood. To find out what is wrong with a child's posture, it is important to find it early. Posture correction is also important for children with posture problems. This counseling aims to teach how to diagnose scoliosis in oneself, prevent it in teenagers and increase awareness and knowledge about maintaining health and good body posture. Scoliosis education methods for children include health promotion, use of posters, pre-tests and post-tests, as well as education about scoliosis. This activity was attended by 27 participants aged 11 - 12 years at SDN Polowijen 1 Malang City. The consequences of this action show an increase in student information about scoliosis with a normal pre-test average of 62.8% to a post-test of 96.2%.